An Improved AC-BM Algorithm for Monitoring Watch List - Tang Jun; Mo Yiwen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the expanding of database of the watch list of anti-money laundering, improving the speed in matching between the watch list and the database of account holders and clients’ transaction is especially important. This paper proposes an improved AC-BM Algorithm, a matching algorithm of subsection, to improve the speed of matching. Experiment results show the time performance of the improved algorithm is better than traditional BM algorithm, AC algorithm and the AC-BM algorithm. It can improve the efficiency of on-line monitoring of anti-money laundering. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.4141